CALCULATION OF RELIABILITY OF LARGE SYSTEMS BASED ON WF-METHOD - Strelnikov , V. P.; Lukyanenko , O. V.; Onoshko, I. V. (Problems of Informatization and Management, 2021)
All known methods for calculating reliability indicators, based on the use of strictly probabilistic models of failure distribution (exponential, Weibull, etc.), allow only two possible states of system elements - serviceable and faulty, the probabilistic combination of which also determines the two-position state of the system as a whole - operable or inoperative. ... The calculation method based on the use of probabilistic physical models differs from strictly probabilistic methods in that it considers a continuous set of states of elements and a system with continuous time and is called the probabilistic physical method (WF method).